Facile, Efficient Diastereoselective Synthesis of Tetrahydroquinoline Scaffolds Using Propylene Carbonate as an Eco-Friendly Solvent - S. B. Forero, Josue; M. de Carvalho, Erika; J. Junior, Joel; M. da Silva, Flavia (Current Organic Synthesis, 2015)
A diastereoselective synthesis of functionalised tetrahydroquinolines was performed using a one-pot imino Diels-Alder cycloaddition reaction of anilines, benzaldehydes and isoeugenol at room temperature using propylene carbonate as an environmentally friendly solvent and molecular iodine as an efficient catalyst. This new protocol has the advantages of higher yields, mild conditions, simple methodology, a short reaction time and a straightforward work-up. Propylene carbonate served as an alternative solvent to the organic solvents commonly used for this reaction, e.g., CH2Cl2, DMF, and MeCN.
Keywords: tetrahydroquinoline